1970
DOI: 10.1002/pol.1970.150080505
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the nonvolatile oxidation products of polypropylene I. Thermal oxidation

Abstract: The nonvolatile products in thermal‐oxidized polypropylene sheet have been quantitatively identified by infrared analysis and chemical reaction. The molecular weight changes with oxidation have been studied by gel‐permeation chromatography. It was determined that there is a functional group at each end of a chain. A general oxidation mechanism scheme for polypropylene is presented. The discovery of γ‐lactone is an indication of the importance of an intramolecular backbiting process. The overall functional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(90 citation statements)
references
References 20 publications
5
84
0
1
Order By: Relevance
“…in agreement with the distribution of carbonyl products determined in the literature in photothermal oxidation [30,[50][51][52][53], in particular from the results of Carlsson and Wiles [1][2][3]. First of all, g 1 was increased up to 0.6, since it was reported that more than half the alkoxy radicals undergo b scission [1,2].…”
supporting
confidence: 77%
“…in agreement with the distribution of carbonyl products determined in the literature in photothermal oxidation [30,[50][51][52][53], in particular from the results of Carlsson and Wiles [1][2][3]. First of all, g 1 was increased up to 0.6, since it was reported that more than half the alkoxy radicals undergo b scission [1,2].…”
supporting
confidence: 77%
“…The rate constants of formation of water, acetone, and acetaldehyde are nearly the same in oxygen (200,400, and 600 torr) and in h e l i~m .~ However, it can be assumed that formation of some other minor products of PP oxidation, e.g., 2-methyl-2-propen-1-01 and l-hydroxy-2-propanone, most likely depends on the presence of oxygen during decomposition of PP hydroperoxide, reactions (23) and (24) and (29) and (30). For instance, decomposition of PP hydroperoxide in an inert atmosphere results in particular in the formation of isobutylene,2O reaction (23), whereas in air 2-methyl-2-propen-1-01 has also been found.…”
Section: Imentioning
confidence: 99%
“…Charring of a polymer under oxygen is a complex process that involves oxidation, the formation of double bonds, cyclization and aromatization [40,41]. PP decomposes via the formation and release of CO, CO2, aldehydes, ketones, carboxylic acids, esters, alkenes, conjugated alkenes and furans [42][43][44]. The FTIR spectra of the volatile decomposition products of PP at maximum release rate are presented in Figure 2.…”
Section: Pyrolysismentioning
confidence: 99%